2016
DOI: 10.1002/chem.201603784
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular trans‐Dicarbofunctionalization of Alkynes by a Formal anti‐Carbopalladation/Stille Cascade

Abstract: An intramolecular Pd-catalyzed trans-dicarbofunctionalization of internal alkynes using aryl bromides and aryl stannanes is presented. Tetrasubstituted double bonds embedded in an oligocyclic ring system are obtained in a regio- and diastereoselective fashion. The transformation features a broad substrate scope and functional-group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…18 With regards to the aryl moiety, alkyl groups at the ortho-, meta-, and para-position relative to the iodide were well tolerated giving a-(2-iodoaryl)enones 15-19 in good to excellent yields. Both an electron-donating methoxy (20) and electron-withdrawing ester (21) could be incorporated, however more strongly electron-withdrawing groups such as -NO2 (22) or -CN (23) led to significant drops in yield. Iterative halogen substitution at the o-, m-, and p-positions was then examined using chlorine, bromine, and fluorine as these products would provide several orthogonal functional handles and be challenging to synthesize using traditional metal catalyzed cross couplings.…”
Section: Modified Strategy Via B-pyridinium Silyl Enol Ethersmentioning
confidence: 99%
See 1 more Smart Citation
“…18 With regards to the aryl moiety, alkyl groups at the ortho-, meta-, and para-position relative to the iodide were well tolerated giving a-(2-iodoaryl)enones 15-19 in good to excellent yields. Both an electron-donating methoxy (20) and electron-withdrawing ester (21) could be incorporated, however more strongly electron-withdrawing groups such as -NO2 (22) or -CN (23) led to significant drops in yield. Iterative halogen substitution at the o-, m-, and p-positions was then examined using chlorine, bromine, and fluorine as these products would provide several orthogonal functional handles and be challenging to synthesize using traditional metal catalyzed cross couplings.…”
Section: Modified Strategy Via B-pyridinium Silyl Enol Ethersmentioning
confidence: 99%
“…Turning to nitrogen-containing scaffolds, conversion to the nitro derivative 43 was of particular interest as this functionality has been utilized in the synthesis of indole natural products and related scaffolds. 3a-3j Initial screening found that typical nitration procedures led to degradation of the enone moiety, 20 however conversion of 12 to the diaryliodonium salt (not shown, see Supporting Information) followed by treatment with KNO2 gave 43 in good yields. 22 Mechanistically, the results are consistent with our initial proposal of an "umpoled" enolonium species which undergoes nucleophilic arylation in the C-C bond forming step (see Scheme 3A), analogous to other recent…”
Section: Modified Strategy Via B-pyridinium Silyl Enol Ethersmentioning
confidence: 99%
“…18 With regards to the aryl moiety, alkyl groups at the ortho-, meta-, and para-position relative to the iodide were well tolerated giving a-(2-iodoaryl)enones 15-19 in good to excellent yields. Both an electron-donating methoxy (20) and electron-withdrawing ester (21) could be incorporated, however more strongly electron-withdrawing groups such as -NO2 ( 22) or -CN ( 23) led to significant drops in yield. Iterative halogen substitution at the o-, m-, and p-positions was then examined using chlorine, bromine, and fluorine as these products would provide several orthogonal functional handles and be challenging to synthesize using traditional metal catalyzed cross couplings.…”
mentioning
confidence: 99%
“…Turning to nitrogen-containing scaffolds, conversion to the nitro derivative 43 was of particular interest as this functionality has been utilized in the synthesis of indole natural products and related scaffolds. 3a-3j Initial screening found that typical nitration procedures led to degradation of the enone moiety, 20 however conversion of 12 to the diaryliodonium salt (not shown, see Supporting Information) followed by treatment with KNO2 gave 43 in good yields. 22 Mechanistically, the results are consistent with our initial proposal of an "umpoled" enolonium species which undergoes nucleophilic arylation in the C-C bond forming step (see Scheme 3A), analogous to other recent reports of reductive [3,3] iodonium-Claisen reactions.…”
mentioning
confidence: 99%
“…[13] It is important to use as ubstituent at the triple bond that does not allow b-hydride elimination, since this pathway is fastert han the internal isomerization.I na ll previous reports, the reactive anti-configured Pd species was intercepted by nucleophilic carbon moieties such as olefins, [15] or stannylateda renes. [16] However,t he use of nucleophilic heteroatomic speciess uch as hydroxy units [17] would allow af acile generationo ft etrasubstituted enol ethers startingf rom internal alkynes. Couplingp artners wouldb eaC ÀBr bond for the first side of the triple bond and aliphatic alcohols or phenolsf or the opposite side, leading to HBr as the only side product.…”
mentioning
confidence: 99%